Atrial fibrillation-related ischemic stroke and cognitive impairment: Research progress on the characteristics and pathogenesis - Xinyi He; Haixing Xiao; Hui Guo; Yizhen Weng; Lulu Zhang; Qi Fang; Xiang Tang (Brain Research Bulletin)
Post-stroke cognitive impairment (PSCI) is a significant neurological complication, affecting up to one-third of stroke survivors. Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia, significantly increasing the risk of ischemic stroke. Increasing evidence suggests that AF plays a pivotal role in exacerbating cognitive decline in stroke patients. This review integrates current clinical, imaging, and mechanistic findings to elucidate how AF-related strokes exacerbate cognitive decline through multiple overlapping pathways, including thromboembolism, neuroinflammation, atherosclerosis, cerebral hypoperfusion, cerebral small vessel disease, and silent infarctions. These processes collectively impair cerebrovascular integrity, induce neuronal damage, and accelerate brain aging. The review further evaluates the role of clinical and neuroimaging biomarkers as predictive tools and their utility in guiding therapeutic strategies. By integrating insights of the latest researches, we aim to provide a comprehensive framework for alleviating cognitive decline in patients with AF-related stroke and highlight future research directions.